Effect of graphene addition on tensile, flexural, and hardness behavior of GFRP composites - Siraganahalli N. Nagesh; Chamarajanagar G. Ramachandra; Pallagatte C. Aruna Kumara; Praveen Kumar Kanti; Chander Prakash; Sandeep Kumar; Gabr Goshu Syum; Archana Bhat (PLoS ONE, 2026)
Polymer Matrix Composites represent a new generation of engineering materials in which matrix materials are altered by reinforcing filler materials to enhance strength and other properties. In the present work, the Glass fiber reinforced polymer (GFRP) composites were fabricated by adding different compositions of Graphene as a Nano filler material using the Hand layup technique, followed by the Vacuum bagging process. The Graphene filler material was varied from 0 wt. %, 2 wt. %, and 4 wt. %. The prepared composites were characterized by subjecting them to various mechanical tests such as tensile test, flexural test, and micro hardness test. The experimental results revealed an increase in tensile strength by 5.48%, flexural strength by 27.74%, and a reduction in microhardness by 20% for 4 wt. % filler added GFRP compared to neat GFRP, indicating reduced brittleness and enhanced ductility. Furthermore, addition of graphene resulted in a 9% increase in elongation and improved interfacial bonding between glass fiber and epoxy matrix was observed. Scanning electron microscopy (SEM) analysis confirmed uniform graphene dispersion, reduced voids, and improved fiber–matrix adhesion. The results demonstrate that the inclusion of 4 wt. % graphene filler achieves an optimal balance between strength, flexibility, and interfacial bonding, making these composites suitable for structural and lightweight applications.